2012
DOI: 10.1038/nm.2609
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of a mutation in the extracellular domain of the Epidermal Growth Factor Receptor conferring cetuximab resistance in colorectal cancer

Abstract: Antibodies against epidermal growth factor receptor (EGFR)--cetuximab and panitumumab--are widely used to treat colorectal cancer. Unfortunately, patients eventually develop resistance to these agents. We describe an acquired EGFR ectodomain mutation (S492R) that prevents cetuximab binding and confers resistance to cetuximab. Cells with this mutation, however, retain binding to and are growth inhibited by panitumumab. Two of ten subjects studied here with disease progression after cetuximab treatment acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
383
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 441 publications
(406 citation statements)
references
References 7 publications
(1 reference statement)
18
383
0
5
Order By: Relevance
“…15,16 More importantly, cetuximab-resistant patients who harbor the S492R mutation responded to treatment with panitumumab. 17 In keeping with the results, Voigt et al 18 revealed that the epitope of panitumumab differs from that of cetuximab, providing a possible explanation for the benefits from panitumumab treatment in some cetuximab-resistant patients. However, as a fully human IgG2 mAb, panitumumab is devoid of natural killer (NK) cellmediated classical ADCC.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…15,16 More importantly, cetuximab-resistant patients who harbor the S492R mutation responded to treatment with panitumumab. 17 In keeping with the results, Voigt et al 18 revealed that the epitope of panitumumab differs from that of cetuximab, providing a possible explanation for the benefits from panitumumab treatment in some cetuximab-resistant patients. However, as a fully human IgG2 mAb, panitumumab is devoid of natural killer (NK) cellmediated classical ADCC.…”
Section: Introductionmentioning
confidence: 56%
“…36,37 However, clinically relevant extracellular domain mutations of EGFR have been shown to mediate resistance to cetuximab but remain sensitive to panitumumab. 17 This mutation may have a role in providing the clinical benefit of panitumumab in a subset of subjects with mCRC who do not respond to treatment with cetuximab. 38 Additionally, Voigit et al 18 described a distinct binding site for panitumumab that is different from that of cetuximab.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] After 48 or 72h incubation, activated PanP-DM1 inhibited the growth of DiFi, H292 and A431 cancer cells in a dose-dependent manner ( Fig 3A). Importantly, the growth inhibition was significantly stronger compared with activated PanP at the concentration of 1 mg/ml (P<0.001).…”
Section: Panp-dm1 Has Superior In Vitro Anti-tumor Activity Compared mentioning
confidence: 93%
“…A recent study reported that cell lines with acquired resistance to cetuximab showed a mutation of the extracellular domain of the EGFR, 1476C>A, leading to a substitution of serine to arginine at amino acid 492 (S492R). 18 This mutation interferes with binding to cetuximab but not to panitumumab. Indeed, cell lines with the EGFR S492R mutation showed sensitivity to panitumumab but not to cetuximab.…”
Section: Introductionmentioning
confidence: 99%